Fabrication of MnO/C composites utilizing pitch as the soft carbon source for rechargeable Li-ion batteries. (24th October 2016) - Zhao, Xin-Yi; Bai, Xue; Yang, Wei; Shen, Dong; Yang, Huan; Lun, Ning; Qi, Yong-Xin; Bai, Yu-Jun
Abstract : MnO nanoparticles coated with pitch-derived soft carbon exhibit greatly enhanced electrochemical performance compared to those coated with glucose-derived hard carbon. Abstract : Manganese oxide was prepared by decomposing MnCO3 obtained from the reaction between Na2 CO3 and MnCl2 ·4H2 O, and a MnO/C composite was fabricated by processing the mixture of manganese oxide and pitch in a nitrogen atmosphere at 600 °C. Compared to the MnO/C composite obtained under the similar conditions using glucose as the carbon source, the composite containing the pitch-derived soft carbon demonstrates an improved initial Coulombic efficiency (from 57.2% to 68.8%), a stable capacity of 601.8 mA h g −1 at 100 mA g −1 after the 50th cycle, an outstanding capacity of 265 mA h g −1 even when cycling at 500 mA g −1 for 350 times, and superior rate capabilities. From the detailed characterization by X-ray diffraction, Raman spectroscopy, transmission electron microscopy and thermogravimetric analysis, it is found that the enhanced electrochemical performance associated with the improved electronic conductivity and high stability resulted from the higher graphitization degree of the pitch-derived soft carbon than the glucose-derived hard carbon.